SPE Improved Oil Recovery Conference 2016
DOI: 10.2118/179535-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of PC-SAFT Equation of State for CO2 Minimum Miscibility Pressure Prediction in Nanopores

Abstract: CO 2 miscible injection is generally one of the most efficient enhanced oil recovery (EOR) methods and widely used in the conventional oil reservoirs. The applicability of CO 2 EOR technology for unlocking the resources from unconventional tight and shale formations and the mechanisms of miscible flooding in these reservoirs still remain unclear. An important parameter used to evaluate the feasibility of CO 2 miscible flooding is the minimum miscibility pressure (MMP). Even though experimental approaches, empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…They found that using the proposed model, the oil-gas MMP decreases with a decreasing pore radius. Similar results have also been observed in the study of Wang et al [27]. They employed the Perturbed-Chain Statistical Associating Fluid Theory (PC-SAFT) [35] to calculate the vapor-liquid IFT with increasing pressure.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…They found that using the proposed model, the oil-gas MMP decreases with a decreasing pore radius. Similar results have also been observed in the study of Wang et al [27]. They employed the Perturbed-Chain Statistical Associating Fluid Theory (PC-SAFT) [35] to calculate the vapor-liquid IFT with increasing pressure.…”
Section: Introductionsupporting
confidence: 84%
“…The essence of this method is that the oil-gas MMP is determined when the vapor-liquid IFT reaches zero. Later, researchers modified this method and used the Parachor model [24] combined with a cubic equation of states to calculate the vapor-liquid IFT to determine the theoretical oil-gas MMP [26][27][28][29]. The original cell-to-cell simulation method was first proposed by Metcalfe et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, MMP changes inconsistently with increasing capillary pressure and may decrease, increase, or remain unchanged for different mixtures. When both capillary force and critical shifts are considered, the MMP of the mixture is reduced by nanopores, but when the pore diameter is greater than 10 nm, the change of MMP can be ignored [109,110]. In immiscible displacement, the capillary pressure effect is useful for enhancing oil recovery.…”
Section: Interfacial Tension and Miscibilitymentioning
confidence: 99%
“…The MMP would be the same as the critical point of this pseudo-binary mixture, at which interfacial tension (IFT), and subsequently gas-oil capillary pressure would be zero. Wang et al [55] developed a Parachor model to account for the effect of confinement on interfacial tensions (IFTs). They used their model to calculate CO 2 MMP of Bakken oil.…”
Section: Sensitivity Analysismentioning
confidence: 99%